Pengaruh SiLPA dan PAD terhadap Serapan Anggaran di Provinsi Lampung - Sekar Sitaresmi; Heru Wahyudi (Penerbit Goodwood, 2022)
Purpose: This study aims to see the effect of SiLPA and PAD on budget absorption in Lampung Province in 15 districts/cities in 2018 Research methodology: The analytical method used in this study is the Panel Data Analysis method with the FEM (Fixed Effect Model) model with the independent variables being the remaining budget for the current year, the remaining budget for the previous yea,r and local revenue. Results: The results of this study indicate that Local Revenue has a positive and significant effect on budget absorption in 15 districts/cities of Lampung Province, and the remaining budget for the current year has a negative and significant effect on budget absorption in 15 districts/cities of Lampung Province, while the remaining budget for the previous year has a negative and insignificant effect. on budget absorption in 15 districts/cities of Lampung province. Limitations: The limitation of this study is that it is only in 15 districts/cities in the province of Lampung and uses 2018 data Contribution: This research is expected to provide input and contribute information in budgeting policy-making and APBD implementation to maximize budget absorption.